SOCIAL INNOVATION: CHARACTERISTICS RELATED TO SUSTAINABLE DEVELOPMENT - Yohani Dominik dos Figueiredo; Márcia Aparecida Prim; Gertrudes Aparecida Dandolini (The Journal of Engineering and Exact Sciences)
Social innovation and sustainable development are topics of research interest for political leaders and civil society players, as well as for scholars from different disciplinary fields. They are presented as an effective, efficient, and sustainable solution to social problems generated by the present. In this sense, this research aims to identify characteristics of social innovation that are associated with sustainable development, from a narrative review of the literature. As a result, it was possible to identify characteristics such as improving quality of life and well-being, social change, innovative nature, among others, which are directly linked to the constructs of sustainable development. Special attention should be paid to the Sustainable Development Goals, which go hand in hand with social innovation actions as a way to reverse the situation of environmental degradation and social indigence.